2020
DOI: 10.21203/rs.3.rs-26074/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 confinement on the time and intensity of physical activity in the Spanish population

Abstract: Background The lockdown and social distancing caused by COVID-19 may influence common healthy behaviour. Due to the unprecedent worldwide confinement in which Spain has been one of the most affected with severe rules governing confinement, physical activity and sedentarism may change due to prolonged stays at home. The aim of this study is to evaluate how physical activity and sedentary time have changed during confinement in the Spanish population. Methods 3800 healthy adults (age ≥ 18 - ≤64 years) residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 12 publications
4
18
3
5
Order By: Relevance
“…These results coincided with those obtained by Castañeda-Babarro et al [ 54 ], who found that PA decreased significantly during lockdown in the entire Spanish population. These authors observed that vigorous PA and walking time decreased by 16.8% and 58.2%, respectively, while sedentarism increased by 23.8%, with these decreases being greater in males than females.…”
Section: Discussionsupporting
confidence: 92%
“…These results coincided with those obtained by Castañeda-Babarro et al [ 54 ], who found that PA decreased significantly during lockdown in the entire Spanish population. These authors observed that vigorous PA and walking time decreased by 16.8% and 58.2%, respectively, while sedentarism increased by 23.8%, with these decreases being greater in males than females.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the previous cross-sectional studies showed reductions in substantial reductions in moderate-intensity physical activity 4,13 , which did not change in the present study. Although differences in age of the population and in study design may not be discharged as reasons for the lower physical activity reduction in the present than previous studies 4,13 , the fact that participants of present study were physically active and participated in an educational program to promote healthy behaviors prior to pandemic should be considered. Educational programs promoting healthy behaviors has shown to be effective in improving physical activity 15,16 .…”
Section: Discussioncontrasting
confidence: 51%
“…During the first months of the outbreak, Spain adopted a strict home lockdown motivated by the pandemic’s severe impact [ 37 ]. Previous studies from Italy and Japan also reported a decrease in PA [ 6 , 14 , 15 , 16 , 17 , 18 , 19 , 38 ]; or a rising prevalence of inactive older persons [ 18 , 19 ]. Despite the similarities in the mobility restriction measures among the three countries, the study populations are different: the Italian study used a cohort that underwent the implantation of a cardio meter-defibrillator before the pandemic [ 14 , 18 ] whereas the one enrolled by Suzuki et al [ 18 ] was discharged from a rehabilitation setting; both samples were significantly younger than ours.…”
Section: Discussionmentioning
confidence: 97%
“…PA has been previously described as a risk factor for frailty [ 8 , 9 , 10 ] and a key component of interventions to prevent or reduce the development and progression of frailty [ 3 , 11 , 12 , 13 ]. It has been estimated that the preventive measures applied during the COVID-19 pandemic led to a 25% reduction of PA in the general population [ 6 , 14 , 15 , 16 , 17 ], and more than 45% in older adults [ 6 , 14 , 15 , 16 , 18 , 19 ]. Despite these data, the possible determinants of this reduction in PA levels have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%